Webern’s “Heavenly Journey” and Schoenberg’s Vagrant Chords - Matthew Shaftel (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2012)
The five Dehmel Lieder (1906–08) act as a bridge in Anton Webern’s musical development. Along with the earliest of the fourteen George Lieder, they represent an initial exploration of a new musical style, while still maintaining substantive ties with the Romantic Lied of Webern’s predecessors. Because the five Dehmel settings are the only songs written by Webern under the direct tutelage of Arnold Schoenberg, they also provide unique insight into Schoenberg’s role as Webern’s teacher at this moment of stylistic shift. This article focuses particularly on the fair copy and sketches of the most extended of the Dehmel songs, “Himmelfahrt,” using linear analysis to show how Webern employed “vagrant” harmonies (in Schoenberg’s terms) and contrapuntal delays of tonal arrivals to arrive at a state of “suspended tonality.” In addition, it engages several markings in the sketches to speculate about Schoenberg’s influence on these songs. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part III).